Nitrogen reactive ion etch processes for the selective removal of poly-(4-vinylpyridine) in block copolymer films. (25th June 2018) - Flynn, Shauna P; Bogan, Justin; Lundy, Ross; Khalafalla, Khalafalla E; Shaw, Matthew; Rodriguez, Brian J; Swift, Paul; Daniels, Stephen; O'Connor, Robert; Hughes, Greg; Kelleher, Susan M
Abstract: Self-assembling block copolymer (BCP) patterns are one of the main contenders for the fabrication of nanopattern templates in next generation lithography technology. Transforming these templates to hard mark materials is key for pattern transfer and in some cases, involves selectively removing one block from the nanopattern. For poly(styrene)- block- poly(4-vinylpyridine) (PS- b -P4VP), a high χ BCP system which could be potentially incorporated into semiconductor nanofabrication, this selective removal is predominantly done by a wet etch/activation process. Conversely, this process has numerous disadvantages including lack of control and high generation of waste leading to high cost. For these reasons, our motivation was to move away from the wet etch process and optimise a dry etch which would overcome the limitations associated with the activation process. The work presented herein shows the development of a selective plasma etch process for the removal of P4VP cores from PS- b -P4VP nanopatterned film. Results have shown that a nitrogen reactive ion etch plasma has a selectivity for P4VP of 2.2:1 and suggest that the position of the nitrogen in the aromatic ring of P4VP plays a key role in this selectivity. In situ plasma etching and x-ray photoelectron spectrometry measurements were made without breaking vacuum, confirming that the nitrogen plasma has selectivity for removal of P4VP over PS.